Analisis Hubungan Pemasaran Online terhadap Keputusan Pembelian pada Toko Akrilik Express.com - Saraswati, Sri; Yuningsih, Noni (Journal of Economics and Business UBS, 2019)
The rapid development of digital technology is supporting the use of Internet is marketing purposes such as corporate promotion by internet to attract customer awerness. PT. Indomika Utama was born on March 2002 as an custome acrylic producer for direct customer. The product has been promoted on line and also using on-line selling process to assist customer convenience and care. Since the product is customer base design (Customization product). This study aims to (1) Know the online relationship to purchasing decisions at the Acrylic express.com store (2) What online affects consumers to make purchasing decisions at express.com acrylic shop. Sampling method used is non probability sampling with sampling method saturated counted 41 respondents. Processed data used simple linear regression analysis. From the research results obtained conclusion that the characteristics of acrylic express store consumers dominated by the age of 26-30 years and female sex. In this study also concluded that online marketing has a relationship of 78.4% to consumer purchasing decisions on express.com acrylic store sites while the remaining 21.6% came from factors not examined in this study. And the tools of online marketing convenience indicators that determine consumers to make purchasing decisions at express.com acrylic stores